Ensuring Effective Public Health Communication: Insights and Modeling Efforts From Theories of Behavioral Economics, Heuristics, and Behavioral Analysis for Decision Making Under Risk - Edwards, Darren J. (Frontiers in Psychology, 2021)
Public health (PH) messaging can have an enormous impact on shaping how individuals within society behave, and can ensure it is in a safe and responsible way, consistent with up-to-date evidence-based public health guidelines. If done effectively, then messaging can save lives and improve the health of those within society. However, unfortunately, those within Government PH bodies typically have little training about how to effectively represent PH messages in a way which is consistent with psychological theories of cognitive bias, in order to avoid cognitively biasing the public through their messages. As a result of this, inadequate representation of PH messages can result which can often lead to cognitive bias in those from the public who read or listen to the message information. This can lead to lead to poor decision making of the pubic as a whole, which can then further lead to harm and even death of public members as a result of these poor decisions. One way to minimize the problem of bias in decision making is to explore psychology theories which model how bias can occur from PH messaging, and identify ways in which PH agencies can utilize such approaches to improve the effectiveness of their messages. Previous focus has been largely on behavioural economic (BE) theories, however, here, other accounts are offered in addition to these, from the behaviour analysis (BA) domain, which may increase the predictive power of modeling bias, and have applications for how best to represent PH message information which minimize bias.